Estudio de Requerimientos Tecnológicos para Implementar un Sistema de Comunicación para las Personas no Videntes del Almacén Créditos Económicos de la Cuidad de Babahoyo. - Estrada Sanchez, Yamally Silvana (2018)
People with visual disabilities face obstacles not only physically, but also in the social sphere. Therefore, they can not benefit from certain services that the company offers, such as access to Commercial Credits. The effect is unfavorable to those who, due to having this type of disability, can not make commercial credits. This does not mean that companies discriminate against people with visual disabilities, but as companies must ensure the integrity of it, making known the content of the documentation that must be signed by customers to access a credit. There are technologies such as "A ring to read any text", where through a camera the ring sends images to a computer that recognizes them and reads aloud. This ring uses algorithms "FingerReader", which consists of giving information at the moment in that the user away from the line that is reading. Another well-known technology is the "tactile" screen capable of creating figures and braille, based on moving parts that up and down are able to form the points to read the symbols forming the words. "This technology was used many years ago by Mr. Edesur, with the advice of the association for help to blind people, they deliver invoices in Braille, this project has 200 customers who use this billing service." (CINTHIA PALACIOS LA NACION)